(untitled) (International Journal of Engineering and Computer Science, 2022)
One of the most recent technological developments, block chain technology has the potential to help a lot of organizations. In order to give readers a better understanding of what block chain technology is and how it works, this paper’s main goal is to give an overview of it. The questions that should be asked to determine whether Block chain Technology is the best option for organizations are included in another section of this paper. This section will also provide a summary of how Block chain Technology can benefit businesses. The discussion that follows demonstrates how various industries are currently mastering the technology in order to dominate their fields. This essay will also look at the findings of a study that was done to gauge public awareness of block chain technology.